Effects of Fipronil Induced Testicular Dysfunction In Male Albino Rats - Payal Malame,; Varsha Dhurvey,; Nayan Kumbhare,; Vaibhavi Ingle,; Prerna Bisen, (The Bioscan, 2025)
Fipronil (FIP), a widely used phenylpyrazole insecticide, has raised significant concerns due to its environmental persistence, bioaccumulation, and potential adverse effect on non-target organisms, including humans. The study investigates the reproductive toxicity of Fipronil in male albino rats, focusing its impact on testicular structure and function. Male rats were administered varying doses of Fipronil to evaluate changes in body weight, testis weight, histopathological alterations, biochemical parameters and hormone levels. Result revealed dose-dependent reduction in body and testis weight, histological damage to seminiferous tubules, disrupted biochemical markers and significant alterations in serum testosterone, FSH and LH levels. These findings underscore Fipronil’s potential to impair male reproductive health through mechanisms involving oxidative stress, hormonal disruption, and structural damage to testicular tissue.